Infrastructure Influence, School Conditions And The Economic Towards School Disputes In Cirebon District - Syaeful Bakhri; Ahmad Amin Mubarok (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
One of the determinants of the Human Development Index (HDI) is the education sector. The condition of education in Indonesia, including in coastal areas such as Cirebon Regency, still finds problems related to the dropout rate. As with the Ministry of Education and Culture data, the Rough Participation Rate from SD to Higher Education in Cirebon Regency is still at number 21 out of 27 cities/regencies in West Java. The purpose of this study was to determine what factors can reduce the dropout rate. This research is a qualitative descriptive study. Resource persons in this study were 22 respondents familiar with the conditions of education in the Cirebon Regency, including elements of the Regional Research and Development Planning Agency, the Education Office, Educators, education, and community leaders who were concerned about education problems. The method used is the Process Hierarchy Analysis (AHP). With this analysis, the researcher tries to arrange policy priorities based on each factor's weight so that a priority scale is obtained to reduce the dropout rate in Cirebon Regency. The results showed that the priority order based on the hierarchy is that the infrastructure factor is the priority with a weight of 24.89%. There are aspects of school conditions 22.38% and economic conditions 19.92%.Â Keywords: Infrastructure, Schools, Economics, and Dropouts